1987
DOI: 10.1139/v87-131
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic study of the reaction between cystine and sulfide in alkaline solutions

Abstract: The reaction between cystine (CySSCy) and hydrogen sulfide ion (HS−) in alkaline solutions has been studied by amino acid analysis and uv–visible spectroscopy. The reaction occurs in two reversible steps to form cysteine (CySH), S-thiocysteine (CySS−), and disulfide (S22−), as represented by the reactions [Formula: see text] and [Formula: see text]. The equilibrium and rate constants were pH dependent due to the presence of various charge types of reactants and products. The rate constants at 25 °C, pH 10.0, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
0

Year Published

1989
1989
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 4 publications
1
19
0
Order By: Relevance
“…As precedent, rate constants of (6.2 Ϯ 0.7) ϫ 10 Ϫ2 and 1.3 ϫ 10 Ϫ2 M Ϫ1 s Ϫ1 have been reported for the reaction of cystine with excess H 2 S in 50 mM borate buffer at pH 10.0 or NaOH 0.1 M, respectively (42). These values are lower, by factors of 15-70, than the pH-independent rate constant determined in this work, (9 Ϯ 2) ϫ 10…”
Section: Resultsmentioning
confidence: 76%
“…As precedent, rate constants of (6.2 Ϯ 0.7) ϫ 10 Ϫ2 and 1.3 ϫ 10 Ϫ2 M Ϫ1 s Ϫ1 have been reported for the reaction of cystine with excess H 2 S in 50 mM borate buffer at pH 10.0 or NaOH 0.1 M, respectively (42). These values are lower, by factors of 15-70, than the pH-independent rate constant determined in this work, (9 Ϯ 2) ϫ 10…”
Section: Resultsmentioning
confidence: 76%
“…Disulfide-containing proteins including insulin, bovine serum albumin (BSA), ribonuclease, chymotrypsinogen A and ovalbumin all react with H 2 S to form hydrodisulfide. The apparent second order rate constants at 25°C were reported as 2.2 M −1 min −1 for cystamine, 0.35 M −1 min −1 for cystine (lower than that from [240]), 2.3 M −1 min −1 for denatured BSA and 4 M −1 min −1 for denatured insulin respectively. The reactions also occur at lower pH between 8 and 9.…”
Section: H2s Reaction With Thiol Derivatives (Or Thiol Reaction Wimentioning
confidence: 69%
“…The reaction is very reversible, the rate constants for the reaction and the reverse reaction were determined as 3.7 ± 0.4 M −1 min −1 and 5.5 ± 0.6 M −1 min −1 respectively at 25 °C, pH 10.0 and ionic strength 0.17 M [240]. A mixture of lipoate (the oxidized disulfide form of dihydrolipoate) and Na 2 S in 0.1 M sodium hydroxide (NaOH) also produces hydrodisulfide as measured by an absorption peak at 335 – 340 nm [241].…”
Section: H2s Reaction With Thiol Derivatives (Or Thiol Reaction Wimentioning
confidence: 99%
See 1 more Smart Citation
“…It has been demonstrated that H 2 S can drastically reduce metabolic demand (1). Similar to nitric oxide, H 2 S exerts protective effects on mitochondrial function and respiration (2). However, a conventional belief is that H 2 S is produced in the cytoplasm resulting from the cytosol localization of H 2 Sgenerating enzymes and is consumed through oxidation in mitochondria (3).…”
mentioning
confidence: 99%